The role of short food supply chains in Kosovo’s agriculture - Gjokaj, Ekrem; Nagy, Henrietta; Krasniqi, Nol; Baer-Nawrocka, Agnieszka (European Spatial Research and Policy, 2025)
Short food supply chains (SFSCs) and local markets, where farmers sell directly to consumers, are expanding across the EU, offering alternatives to conventional food chains that limit small farmers’ bargaining power and consumer traceability. In the EU, 15% of farms sell over half of their production directly. For Kosovo’s agricultural sector, SFSCs present new opportunities. This study examines SFSCs in Kosovo using data from 2,500 respondents. The findings show that 54% rely on oral contracts, 20% on written agreements, and distributors use multiple sourcing channels. SFSCs can enhance sustainability, trust, equality and growth in agriculture, business, and rural policy.